Entrustable Professional Activities for Chinese Standardized Residency Training in Pediatric Intensive Care Medicine - Yun, Zhang; Jing, Liu; Junfei, Chen; Wenjing, Zhang; Jinxiang, Wu; Tong, Yue; Aijun, Zhang (Frontiers in Pediatrics, 2022)
Background: Entrustable professional activities (EPAs) was first introduced by Olle ten Cate in 2005. Since then, hundreds of applications in medical research have been made by researchers. There is limited studies in pediatric postgraduate education about EPAs. Methods: A pilot study was implemented in Qilu Hospital of Shandong University Standardized Residency Training in pediatric intensive care medicine. An 8-scale EPAs composed with 15-category EPAs assessment electronic survey was conducted including director-assessments and residents self-assessments. Results: There were totally 217 director-assessment and 44 self-assessment questionnaires, both with rising trend as postgraduate year grows. There was significantly differences between PGY1-PGY2 and PGY1-PGY3 , whereas none differences between PGY2-PGY3 in director-assessing scores. PGY have significant effect on scores of each EPA, whereas position obviously affects scores of all EPAs except EPA1(Admit a patient) and EPA2(Select and interpret auxiliary examinations). Besides, gender only significantly affects scores of EPA6(Report a case), EPA12(Perform health education) and EPA13(Inform bad news). Conclusions: This study indicated that in Chinese Standardized Residency Training in pediatric intensive care medicine, the EPAs assessments have a certain discriminating capability, rising as a relatively obviously trend as PGY grows. Postgraduate year, gender and residents position have effect on EPAs scores to a certain extent. For the inconsistency between residents and director scores, well feedback programme is needed in the future.